Herbal medicines used in the treatment of non-communicable chronic diseases (Research, Society and Development, 2022)
Chronic non-communicable diseases are conditions of continuous character and with a high prevalence in world society. Therefore, there is a series of treatments available on the market to treat these conditions, one of these alternatives being the use of herbal medicines. Thus, this research aimed to identify from the scientific literature the herbal medicines used in chronic non-communicable diseases in the national territory. An integrative literature review was carried out following the 6 steps of Botelho, Cunha and Macedo (2011). The review was based on the question: Which herbal medicines are being used in the treatment of DCNS and which of these diseases have a higher prevalence of use of this class of medicines?. The bibliographic survey took place from August to September 2021, using the database of the virtual health library (VHL) considering the following databases: Latin American Literature in Health Sciences (LILACS) and Medline (Medical Literature Analysis and Retrieval System online). The SCIELO library is used as a third source of data to collect these articles. Thus, this study can identify in the literature the herbal medicines and plants that are used in the national territory, as well as their pharmacological characteristics and action on CNCDs. It was possible to identify studies that address the use of plants in systemic arterial hypertension, diabetes mellitus and obesity, with a variety of species used and forms of preparation. It is worth highlighting as a limitation of this study the limited number of articles that address this issue. Thus, the recognition of the popular use of these drugs and plants can boost their correct, safe and scientific use, in addition to making health professionals aware of the effectiveness of this therapy and the possibility of its use.